Membrane quantum particle swarm optimisation for cognitive radio spectrum allocation. (4th June 2012) - Gao, Hongyuan; Cao, Jinlong; Zhao, Yuning
To design a novel intelligence algorithm for spectrum allocation problem, a membrane quantum particle swarm optimisation (MQPSO) is proposed. The proposed MQPSO algorithm applies the theory of membrane computing to quantum particle swarm optimisation (QPSO), which is an effective discrete optimisation algorithm. Then the proposed MQPSO algorithm is used to solve spectrum allocation problems of cognitive radio system. By hybridising the QPSO and membrane theory, the quantum state and measure state of the quantum particle can be well evolved in membrane structure. The new spectrum allocation algorithm can search global optimal solution. Simulation results for cognitive radio system are provided to show that the designed spectrum allocation method is superior to some previous spectrum allocation algorithms.